Preventing the spread of COVID-19: Participation in the mass vaccination movement in Magelang Regency - Zulfikar Bagus Pambuko; Suherman Suherman; Mei Lala Sari; Daffa Adi Praditama; Kharisma Amelia Nur’Aini; Trianda Pratiwi (Universitas Muhammadiyah Magelang, 2022)
This community service aims to aid in the prevention of Covid-19 transmission and the success of the vaccination acceleration program for residents of the Magelang Regency. The Subdistricts of Pakis, Tegalrejo, Mertoyudan, Mungkid, Muntilan, Dukun, Sawangan, and Tempuran are some of the areas that are supported in the administration of mass vaccination. Furthermore, this vaccination program has the potential to improve health quality while also restoring community productivity. The service team has been involved in assisting and facilitating health workers, beginning as a vaccine administrator, inputting vaccine data, and finally recording vaccine recipients.